Diagnostic performance of S100B as a rule-out test for intracranial pathology in head-injured patients presenting to the emergency department who meet NICE Head Injury Guideline criteria for CT-head scan. Issue 3 (2nd November 2022) - Rogan, Alice; Sik, Annabelle; Dickinson, Emily; Patel, Vimal; Peckler, Brad; McQuade, David; Larsen, Peter D
Abstract : Background: Traumatic brain injury is a common ED presentation. CT-head utilisation is escalating, exacerbating resource pressure in the ED. The biomarker S100B could assist clinicians with CT-head decisions by excluding intracranial pathology. Diagnostic performance of S100B was assessed in patients meeting National Institute of Health and Clinical Excellence Head Injury Guideline (NICE HIG) criteria for CT-head within 6 and 24 hours of injury. Methods: This multicentre prospective observational study included adult patients presenting to the ED with head injuries between May 2020 and June 2021. Informed consent was obtained from patients meeting NICE HIG CT-head criteria. A venous blood sample was collected and serum was tested for S100B using a Cobas Elecsys-S100 module; >0.1 µg/mL was the threshold used to indicate a positive test. Intracranial pathology reported on CT-head scan by the duty radiologist was used as the reference standard to review diagnostic performance. Results: This study included 265 patients of whom 35 (13.2%) had positive CT-head findings. Within 6 hours of injury, sensitivity of S100B was 93.8% (95% CI 69.8% to 99.8%) and specificity was 30.8% (22.6% to 40.0%). Negative predictive value (NPV) was 97.3% (95% CI 84.2% to 99.6%) and area under the curve (AUC) was 0.73 (95% CI 0.61 to 0.85; p=0.003). Within 24 hours of injury, sensitivity was 82.9% (95% CI 66.4% to 93.44%) and specificity was 43.0% (95% CI 36.6% to 49.7%). NPV was 94.29% (95% CI 88.7% to 97.2%) and AUC was 0.65 (95% CI 0.56 to 0.74; p=0.046). Theoretically, use of S100B as a rule-out test would have reduced CT-head scans by 27.1% (95% CI 18.9% to 36.8%) within 6 hours and 37.4% (95% CI 32.0% to 47.2%) within 24 hours. The risk of missing a significant injury with this approach would have been 0.75% (95% CI 0.0% to 2.2%) within 6 hours and 2.3% (95% CI 0.5% to 4.1%) within 24 hours. Conclusion: Within 6 hours of injury, S100B performed well as a diagnostic test to exclude significant intracranial pathology in low-risk patients presenting with head injury. In theory, if used in addition to NICE HIGs, CT-head rates could reduce by one-quarter with a potential miss rate of <1%.